2014
DOI: 10.1155/2014/234565
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Biological Stress and Mucosal Immunity during a Week Leading to Competition in Adolescent Swimmers

Abstract: In this study we examined changes in the salivary concentrations of immunoglobulin A (sIgA), cortisol (sC), testosterone (sT), and testosterone-to-cortisol ratio (T/C) in 21 competitive swimmers, 11–15 years old, during a week leading to competition as compared to a control (noncompetition) week. No day-to-day changes or significant differences between weeks were observed for sIgA (47.9 ± 4.4 versus 54.9 ± 5.2 μg/mL for control versus competition week, resp.), sC (2.7 ± 0.2 versus 2.5 ± 0.2 ng/mL for control v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(38 reference statements)
4
5
0
Order By: Relevance
“…S-IgA average values before and after training were significantly higher in competitive athletes than in non-competitive swimmers. The results of this study confirmed the majority of studies in that acute bouts of exercise reduced S-IgA levels in a variety of endurance sports, including swimming 7 , 8 , 16 , 25 , 28 . These results contrasted with some authors who indicated that there are no differences in salivary concentrations of S-IgA between athletes and non-athletes, except when athletes are engaged in heavy training 13 , 25 .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…S-IgA average values before and after training were significantly higher in competitive athletes than in non-competitive swimmers. The results of this study confirmed the majority of studies in that acute bouts of exercise reduced S-IgA levels in a variety of endurance sports, including swimming 7 , 8 , 16 , 25 , 28 . These results contrasted with some authors who indicated that there are no differences in salivary concentrations of S-IgA between athletes and non-athletes, except when athletes are engaged in heavy training 13 , 25 .…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study confirmed the majority of studies in that acute bouts of exercise reduced S-IgA levels in a variety of endurance sports, including swimming 7 , 8 , 16 , 25 , 28 . These results contrasted with some authors who indicated that there are no differences in salivary concentrations of S-IgA between athletes and non-athletes, except when athletes are engaged in heavy training 13 , 25 . Several studies demonstrated that S-IgA concentration changes and in particular an absolute concentration of less than 40 mg/L was reported to relate to increased Upper Respiratory Tract Infection (URTI) incidence in athletes 28 .…”
Section: Discussionsupporting
confidence: 87%
“…It has been established that elevated cortisol levels at rest can reflect long-term training stress (38,39) while the testosterone to cortisal ratio has been proposed to indicate the balance between anabolic and catabolic activity. Many researchers suggest that a decrease of 30% or more implies overtraining and/or an unfavored level of anabolic to catabolic hormonal balance (8,40).…”
Section: Discussionmentioning
confidence: 99%
“…Each surgeon has been checked for the eventual presence of upper respiratory tract infection (URTI). We used sC and sIgA ELISA kit (Salimetrics, Pennsylvania, USA), while saliva samples were treated according to the protocols previously described by Papadopoulos et al [22] .…”
Section: Methodsmentioning
confidence: 99%